CuCrO2 Delafossite: A Stable Copper Catalyst for Chlorine Production1. Issue 37 (20th June 2013) - Amrute, Amol P.; Larrazábal, Gastón O.; Mondelli, Cecilia; Pérez‐Ramírez, Javier
<x xml:space="preserve">Abstract</x> With time comes wisdom: Since the implementation of CuCl2 for HCl oxidation by Deacon in 1868, the search for stable copper catalysts has been futile. Cuprous delafossite, CuCrO2 (see picture), is shown to have unprecedented stability against chlorination, allowing for durable Cl2 production with no metal loss. Based on this, a highly active CuCrO2‐CeO2 composite was developed, a cost‐effective Cl2 recovery method.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>